Gliotransmission by Prostaglandin E2: A Prerequisite for GnRH Neuronal Function? - Clasadonte, Jerome; Sharif, Ariane; Baroncini, Marc; Prevot, Vincent (Frontiers in Endocrinology, 2011)
Over the past four decades it has become clear that prostaglandin E2 (PGE2), a phospholipid-derived signaling molecule, plays a fundamental role in modulating the GnRH neuroendocrine system and in shaping the hypothalamus. In this review, after a brief historical overview, we highlight studies revealing that PGE2 released by glial cells such as astrocytes and tanycytes is intimately involved in the active control of GnRH neuronal activity and neurosecretion. Recent evidence suggests that hypothalamic astrocytes surrounding GnRH neuronal cell bodies may respond to neuronal activity with an activation of the erbB receptor tyrosine-kinase signaling, triggering the release of PGE2 as a chemical transmitter from the glia themselves, and, in turn, leading to the feedback regulation of GnRH neuronal activity. At the GnRH neurohemal junction, in the median eminence of the hypothalamus, PGE2 is released by tanycytes in response to cell-cell signaling initiated by glial cells and vascular endothelial cells. Upon its release, PGE2 causes the retraction of the tanycyte end feet enwrapping the GnRH nerve terminals, enabling them to approach the adjacent pericapillary space and thus likely facilitating neurohormone diffusion from these nerve terminals into the pituitary portal blood. In view of these new insights, we suggest that synaptically-associated astrocytes and perijunctional tanycytes are integral modulatory elements of GnRH neuronal function at the cell soma/dendrite and nerve terminal levels, respectively.